Miskonsepsi Siswa SMP Dalam Memahami Ciri-ciri Bangun Segi Empat - Agustyarini, Yhasinta; Ningrum, Rachmania Widya (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2023)
In this study, this qualitative research aimed to describe the misconceptions students of junior high school in understanding characteristics of quadrilateral plane figure. The misconceptions instrument were administered to three students in 8th grade of junior high school. Students understanding were analyzed by misconceptions test with CRI (Certainty of Response Index) method with interviews. The misconceptions in understanding the characteristics of quadrilateral plane figure (trapezoid and parallelogram) were the main result of this study. Students showed the same misconceptions in understanding the characteristics of quadrilateral plane figure. The first, Students assumed the diagonal trapezoid isosceles is the only a pairs of same length segment. The second, students only known the parallelogram and rectangle shape are in the regular quadrilateral shape (if the parallelogram and rectangle has different position or irregular shape then it is no called a quadrilateral). In particular, the results indicated that the students had misconceptions in understanding characteristics of quadrilateral plane figure. The misconception occurs because the ability of student understanding is low or incomplete. So, the teacher should gave more problem and images for understanding the characteristics of plane figure.